The donkey - Shaheen, safdar (Children publications; Karachi, 2008)
"The Donkey by Quran Stories for Children" is a child-friendly retelling of the Quranic parable of the donkey, conveying lessons about knowledge, wisdom, and the importance of understanding beyond appearances.